Publicidad sexista transmitida en la televisión ecuatoriana: Imaginarios sociales en los adolescentes. - Almeida Zapata, Mishel Dolores (2018)
The present paper will announce which are the social imaginaries of adolescents from the Educational Unit "Jean Piaget" advertising in cleaning products. The objectification of the female body is expressed regularly in the advertisements of cleaning products, the estereotiparla as the perfect housewife. The objectives of this research are framed in determining the social imaginaries of adolescents from the sexist advertisements of cleaning products, this way to be able to categorize them within gender and thus know if men or women distinguished faster this type of advertisements to finish with the objectives is designed an educational campaign with the adolescent students of the institution, with the purpose of obtaining the imaginaries of the adolescents compared to this subject. The methodology to be implemented is qualitative focus group will be used, since with this technique, the participants are subject to live a reality and to the interpretative understanding of the human experience The importance of this project is to analyze an idea pre established about what they think adolescents in an institution with stereotyped gender biases about sexist advertising in cleaning products. The direct beneficiaries are the adolescent students at the Educational Unit "Jean Piaget", since a previous survey was unable to determine the existence of gender stereotypes. The indirect beneficiaries are the residents of the city of Latacunga, since there is not an investigation of this nature within the city. As a result of this investigation it was found that for every 16 adolescents two maintain the naturalization of the image objectification from women in advertising of cleaning products these data were obtained by means of the application of two focus groups for adolescents from Educational Unit "Jean Piaget".